Linking the timing of a mother's and child's death: comparative evidence from two rural South African population-based surveillance studies, 2000-2015 - Houle, B; Kabudula, CW; Stein, A; Gareta, D; Herbst, K; Clark, SJ (Public Library of Science, 2021)
Background: The effect of the period before a mother’s death on child survival has been assessed in only a few studies. We conducted a comparative investigation of the effect of the timing of a mother’s death on child survival up to age five years in rural South Africa.